A single-photon server with just one atom - Hijlkema, M; Weber, B; Specht, H; Webster, S; Kuhn, A; Rempe, G (2007)
Neutral atoms are ideal objects for the deterministic processing of quantum information. Entanglement operations have been carried out by photon exchange or controlled collisions, and atom-photon interfaces have been realized with single atoms in free space or strongly coupled to an optical cavity. A long-standing challenge with neutral atoms, however, is to overcome the limited observation time. Without exception, quantum effects appeared only after ensemble averaging. Here, we report on a single-photon source with one, and only one, atom quasi-permanently coupled to a high-finesse cavity. 'Quasi-permanent' refers to our ability to keep the atom long enough to, first, quantify the photon-emission statistics and, second, guarantee the subsequent performance as a single-photon server delivering up to 300,000 photons for up to 30 s. This is achieved by a unique combination of single-photon generation and atom cooling. Our scheme brings deterministic protocols of quantum information science with light and matter closer to realization. ©2007 Nature Publishing Group.